GRANULAR ENRICHED-COMPOST FROM ORGANIC WASTE CAMPUS AS SOIL CONDITIONER IN INTENNSIVE RICE FARMING SYSTEM - Azizah, Nur; Prasetya, Budi; Kurniawan, Syahrul (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
Â Effort to reduce the high dependence of farmers on inorganic fertilizers is introducing compost as soil conditioner. The objectives of this research are to create enriched granular-compost (EGC) and to test its effect on nutrient availability, plant growth, and grain yield in intensive farming systems. The research was conducted in two consecutive years (2011-2012), consisting of three steps: production of EGC, incubation and field experiment. Incubation experiment was designed by randomized complete design with 5 treatments (control, 4, 6, 8, and 12 Mg ha-1), and the design of field experiment was randomized block design with 7 treatments (control, inorganic fertilizer (IF), 25% EGC + 75% IF, 50% EGC + 50% IF, 75% EGC + 25% IF, 100% EGC + 100% IF and 100% EGC). The results showed that application of EGC increased total-N and P-available 12.5% and 33% respectively on the 10th day after incubation. The highest grain yield (6.13 Mg ha-1) was gained from the application of 100% EGC + 100% IF. The productivity of rice is closely related to the number of productive panicles per plant (r = 0.507*) and percent of filled grain (r = 0.685*).Â Â Keywords: enriched granular-compost, nutrient availability, grain yield